High-Performance Work System and Self-Efficacy on Academic Performance: Work-Life Balance as Mediator - Zami, Imel Nabila Zam; Fajri, Annisa; Alim, Muchammad Rully Sjahirul (Research Horizon, 2026)
The background of the study stems from the increasing number of employee-level students facing dual role pressures between work and study, necessitating a deeper understanding of the factors influencing their academic success. This study aims to analyze the influence of high performance work system and self-efficacy on the academic performance of employee-level students in Semarang City, with work-life balance as a mediating variable. The research method used a quantitative approach with an explanatory design and involved 100 employee-level management students as respondents. Data analysis was conducted using SEM-PLS through SmartPLS. The results showed that HPWS and self-efficacy had a positive and significant effect on work-life balance and academic performance. In addition, work-life balance was shown to have a partial mediating role in the relationship between HPWS and self-efficacy with academic performance. These findings confirm that employee-level students’ academic performance is influenced not only by institutional support and self-efficacy, but also by their ability to maintain role balance. This study provides a theoretical contribution by expanding the application of the HPWS concept in the context of higher education and provides a practical contribution to universities in designing learning support that is adaptive to the needs of employee-level students.